2020
DOI: 10.14207/ejsd.2020.v9n3p215
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Fiscal Decentralization on Economic Growth in Central and Eastern Europe

Abstract: In this research, we evaluated the impact of fiscal decentralization on GDP per capita growth. Using the unbalanced panel data, the authors assessed the interconnections between fiscal decentralization – considering its expenditure and revenue aspects as well as tax autonomy – and economic growth for Central and Eastern European countries from 1995 to 2018. In the examined states, the expenditure decentralization exceeded the revenue one. We found out that revenue decentralization and tax autonomy adversely af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Studies like (Slavinskarite, 2017), [20,21] have empirically proven that developed economies of Europe have a higher degree of fiscal decentralization and more power for financial solutions than the emerging countries. In terms of economic growth, Chugunoy, Makohon and Krykun [22], as well as Korotun, Keneva, Drepin, Levaleva and Kucherenko, [17] investigated the impact of fiscal decentralization on economic growth and GDP per capita growth of emerging markets respectively. Similarly, Permai, Christina, and Gunawan [23] investigated the effect of fiscal decentralization indicators on regional economic performance and found spatial dependencies and spatial heterogeneity on economic performance between locations that affect economic performance using geographically weighted regression (GWR).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies like (Slavinskarite, 2017), [20,21] have empirically proven that developed economies of Europe have a higher degree of fiscal decentralization and more power for financial solutions than the emerging countries. In terms of economic growth, Chugunoy, Makohon and Krykun [22], as well as Korotun, Keneva, Drepin, Levaleva and Kucherenko, [17] investigated the impact of fiscal decentralization on economic growth and GDP per capita growth of emerging markets respectively. Similarly, Permai, Christina, and Gunawan [23] investigated the effect of fiscal decentralization indicators on regional economic performance and found spatial dependencies and spatial heterogeneity on economic performance between locations that affect economic performance using geographically weighted regression (GWR).…”
Section: Literature Reviewmentioning
confidence: 99%
“…"To enhance economic growth and development potentials, developing countries have embraced the decentralization of public spending and revenue collection from governments to subnational government" (Aigbokhan,1999) "Thus, the issue of tax jurisdictions, expenditure assignment and which tier of government can best deliver social services to accelerate economic development continues to be the focus of active and extensive research" [2]. Although, fiscal decentralization has the risks of horizontal fiscal imbalances, but it could increase the capacity and efficiency for high-quality public goods and services [17].…”
Section: Introductionmentioning
confidence: 99%
“…However, to achieve these goals, local governments must also be well organized, which means that political decentralization must be followed by appropriate fiscal decentralization. Korotun et al (2020) assessed the impact of fiscal decentralization on GDP per capita growth for 13 countries in Central and Eastern Europe. The authors found that revenue decentralization and tax autonomy had a negative impact on economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In its development, fiscal decentralization then developed into the core of the implementation of regional autonomy itself. Even through a process of responsible fiscal decentralization, local governments will be able to increase economic growth and welfare of their people (Oates, 1993;Ganaie et al, 2018;Sasana, 2019;De Siano and D'uva, 2017;Aslim and Neyapti, 2017;Korotun, et al, 2020). The concept of decentralization is also expected to be better able to succeed development goals through the provision of control rights to people who have information and incentives to make decisions that are in accordance with their needs so that they are expected to improve the quality and efficiency of public services, in order to fulfill sectoral services and obligations to the community (Hirawan, 2007; Bardhan and Christopher, 1999;Hanif, Wallace, and Gago-de-Santos, 2020).…”
Section: Introductionmentioning
confidence: 99%